Rapid quantification of tenofovir in umbilical cord plasma and amniotic fluid in hepatitis B mono‐infected pregnant women during labor by ultra‐performance liquid chromatography/tandem mass spectrometry. (28th February 2020) - Ma, Zhiyuan; Li, Siying; He, Daqiang; Wang, Yuqing; Jiang, Huidi; Zhou, Hui; Jin, Jie; Lin, Nengming
Abstract : Rationale: Tenofovir (TFV) is a first‐line antiviral agent against hepatitis B virus (HBV) and is recommended for the prevention of mother‐to‐infant transmission of HBV. To study the distribution of TFV in umbilical cord plasma and amniotic fluid of HBV‐infected pregnant women, a rapid and sensitive method for TFV determination was developed and validated. Methods: The quantification method was developed using liquid chromatography coupled to tandem mass spectrometry (LC/MS/MS). The analytes were separated on an Acquity UPLC HSS T3 column under gradient elution with methanol and 0.01% ammonia solution in 10 mM ammonium acetate/water. This is the first reported method for the determination of TFV using alkaline rather than acidic mobile phases. Linearity, accuracy, precision, limit of quantification, specificity and stability were assessed. Results: Detection of TFV was achieved within 4 min. The calibration curves for TFV quantification showed excellent linearity in the range of 1–500 ng/mL. The intra‐ and interbatch precision and accuracy ranged from −4.35% to 6.92%. This method was successfully applied to determination of samples from 50 HBV mono‐infected women undergoing tenofovir disoproxil fumarate therapy. The mean concentrations of TFV in the umbilical cord and amniotic fluid samples were 29.2 (4.6–86) and 470.9 (156–902) ng/mL, respectively, which showed a moderate positive correlation (r = 0.5299, P <0.001). Conclusions: A simple, rapid but sensitive bioanalytical method to determine TFV concentration in both umbilical cord plasma and amniotic fluid using LC/MS/MS was developed and applied to HBV‐infected women during labor who were undergoing TDF therapy, which will help us understand the efficacy and safety of tenofovir during pregnancy.